2018
DOI: 10.3390/ijerph15102265
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Decomposition of Efficiency Differences in Chinese Provincial Community Health Services

Abstract: The objective of this paper is to analyze the provincial efficiency of the Chinese community health care service and its differences. This study allows us to predict the provincial differences in the efficiency of the Chinese community health care service from 2017 to 2026. This study analyzes the contributions of inter-regional and intra-regional differences in the total efficiency difference. We use the Super-SBM (Slacks-based Model) data envelopment analysis (DEA) model, Grey Model GM (1,1) for grey predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Other scholars have estimated the public health efficiency in Greece [ 32 ], India [ 33 ], Lebanon [ 34 ], México [ 35 ], and Slovakia [ 36 ]. Some scholars have deeply discussed China’s public health efficiency, and respectively calculated and studied the Chinese provincial community health service efficiency [ 37 , 38 , 39 , 40 , 41 , 42 ] and the allocation efficiency of the public health resources in the coastal provinces of China [ 43 ]. A few scholars have preliminarily analyzed the allocation efficiency of the rural public health resources [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars have estimated the public health efficiency in Greece [ 32 ], India [ 33 ], Lebanon [ 34 ], México [ 35 ], and Slovakia [ 36 ]. Some scholars have deeply discussed China’s public health efficiency, and respectively calculated and studied the Chinese provincial community health service efficiency [ 37 , 38 , 39 , 40 , 41 , 42 ] and the allocation efficiency of the public health resources in the coastal provinces of China [ 43 ]. A few scholars have preliminarily analyzed the allocation efficiency of the rural public health resources [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, the research results of scholars such as Kawaguchi [ 9 ], Jat [ 17 ], Li [ 22 ], Liu [ 37 ], and Xue [ 45 ] on the measurement of the allocation efficiency of the public health resources and its influencing factors provide a great deal of experience as a reference for the study of this paper. Compared with the existing studies, this paper has three main contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars usually evaluate PHC from two perspectives-institutions and regions-and some scholars evaluate the specific services, such as oral health care in PHC [17][18][19]. In China, studies from the perspectives of institutions and provinces have shown that the efficiency of PHCIs is low [20][21][22][23]. However, there are few studies that have evaluated the efficiency of PHCIs from the perspective of counties.…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies mainly summarized the history and development of Chinese primary healthcare (2,3,25) , and evaluated the fairness of resource allocation and utilization of primary healthcare service. (26)(27)(28)(29)(30) However, due to the lack of support for the projects from the government, the lack of attention from researchers and other reasons, there have been few studies focusing on whether the role of primary healthcare in the overall health system is strengthened, which is the core goal of this round of health reform in China.…”
Section: Introductionmentioning
confidence: 99%